2020
DOI: 10.3390/ijerph17186645
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Persistent Uncontrolled Asthma Symptoms in Community Members Exposed to World Trade Center Dust and Fumes

Abstract: The destruction of the World Trade Center (WTC) towers on the 11th of September, 2001 released a vast amount of aerosolized dust and smoke resulting in acute and chronic exposures to community members as well as responders. The WTC Environmental Health Center (WTC EHC) is a surveillance and treatment program for a diverse population of community members, including local residents and local workers with WTC dust exposure. Many of these patients have reported persistent lower respiratory symptoms (LRS) despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…Despite these limitations, the FDNY WTC Health Program is a valuable resource for understanding irritant‐induced conditions such as accelerated‐FEV 1 ‐decline in an occupational setting where there is otherwise little available data. Even with the unique aspects of the FDNY WTC‐exposed cohort, findings in this population have been replicated in other WTC‐exposed cohorts 30–34 …”
Section: Discussionmentioning
confidence: 76%
“…Despite these limitations, the FDNY WTC Health Program is a valuable resource for understanding irritant‐induced conditions such as accelerated‐FEV 1 ‐decline in an occupational setting where there is otherwise little available data. Even with the unique aspects of the FDNY WTC‐exposed cohort, findings in this population have been replicated in other WTC‐exposed cohorts 30–34 …”
Section: Discussionmentioning
confidence: 76%
“…This study includes a predominately male cohort of previously healthy firefighters which may limit the generalizability of our findings. Nevertheless, many discoveries in the FDNY cohort have been replicated in other WTC exposed populations 5,6,24–26 . Another limitation was that we could not fully determine the degree to which regression to the mean or selection by indication biases, which were produced by the different endotypes, may have accounted for the diminished effect between ICS/LABA initiation and change in FEV 1 ‐slope.…”
Section: Discussionmentioning
confidence: 97%
“…Another study on the WTC Survivors examined the persistence of lower respiratory symptoms (LRS) of uncontrolled asthma affecting individuals residing in lower Manhattan with previous WTC exposure to airborne particles. Reibman et al [ 15 ] reported that out of 60 patients seen at the EHC, who were uncontrolled at baseline, only 11 participants (18%) gained controlled status as defined by the Asthma Control Test after a three-month run-in period on high-dose inhaled corticosteroid and long-acting bronchodilator. After the treatment, uncontrolled subjects showed higher rates of upper airway symptoms, whereas controlled subjects showed persistent bronchial hyper-reactivity (BHR) and upper airway hyper-reactivity as measured by paradoxical vocal fold movement (PVFM).…”
Section: Lung Diseasementioning
confidence: 99%